2014
DOI: 10.1055/s-0034-1389090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Natural Surfactants for Pulmonary Hemorrhage in Very Low-Birth-Weight Infants: A Randomized Controlled Trial

Abstract: Both natural surfactants improved oxygenation when administered for pulmonary hemorrhage in VLBW infants. The type of surfactant seems to have no effect on BPD and mortality rates in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…In another clinical trial by Bozdag et al. they concluded that both Curosurf and Survanta improved oxygenation in VLBW infants with pulmonary hemorrhage but there was no difference for these two drugs for effectiveness on BPD as well as mortality rate [17] . Terek et al., comparing effectiveness of Curosurf and Survanta in preterm infants with RDS, mentioned that improvement of perfusion index (PI) was achieved earlier in Survanta group in comparison with Curosurf group.…”
Section: Discussionmentioning
confidence: 99%
“…In another clinical trial by Bozdag et al. they concluded that both Curosurf and Survanta improved oxygenation in VLBW infants with pulmonary hemorrhage but there was no difference for these two drugs for effectiveness on BPD as well as mortality rate [17] . Terek et al., comparing effectiveness of Curosurf and Survanta in preterm infants with RDS, mentioned that improvement of perfusion index (PI) was achieved earlier in Survanta group in comparison with Curosurf group.…”
Section: Discussionmentioning
confidence: 99%
“…There are few clinical trials supporting surfactant use in pneumonia [168], although in a recent observational study babies with RDS complicated by pneumonia seemed to require more surfactant [169]. Surfactant therapy improves oxygenation in babies with pulmonary haemorrhage, and although there are no RCTs looking at outcomes compared with no treatment [170], a recent small trial comparing two different natural surfactant preparations in pulmonary haemorrhage showed more rapid improvement in oxygenation with poractant alfa compared with beractant, but with no differences in other outcomes [171]. There are no data to support routine or rescue use of inhaled nitric oxide (iNO) in preterm babies [172].…”
Section: Managing Blood Pressure and Perfusionmentioning
confidence: 99%
“…Coagulopathy is commonly described in conjunction with PH. 1 Vitamin K was administered in a prospective RCT 8 (n = 42) and a retrospective case series 9 (n = 27) in combination with vasopressors to all neonates studied, although the rationale for this was not described. Neither study evaluated the effectiveness of administration of vitamin K or the vasopressor in inducing cessation of PH or achieving favourable outcomes.…”
Section: Coagulopathymentioning
confidence: 99%